Research on Real-Time Optimal Path Algorithm of Urban Transport - Jie Zhang; Jianchun Li; Xiaoyan Fan; Zhuo Deng (Institute of Advanced Engineering and Science, 2014)
Based on the ant colony algorithm, urban real-time traffic optimal path algorithm was designed through restricting search area and search direction of ant colony system, making the real-time traffic and distance as the optimal path weights and regarding intersection turning as the impact of weight value combined with Chinese situation. The algorithm could calculate the optimal path through algorithm complexity test. We obtained a traffic optimal path with timeliness and practical value combined with ant colony algorithm considering multiple parameters.The obtained path enabled user to reach destination within a short time and with the least fuel through actual traffic test. It was regarded as the optimal path. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.3535